Ethics and clinic in psychosocial care: contributions of Freud's and Lacan's psychoanalysis - Costa-Rosa, Abílio (Saúde e Sociedade, 2011)
The main objective is to discuss the possibility of an ethics that is relevant to the set of actions currently performed in the perspective of Psychosocial Care in the field of Public Mental Health. Using the essay method, I will start with the analysis of some important propositions about ethics in Mental Health, present in the recent literature, and with my many years of experience in the field of psychosocial care as a worker, as a clinical and institutional advisor with the Ministry of Health, and as a psychotherapist trainer. Two methods of analysis are considered: disciplinary ethics, called psychiatry ethics, including a major attempt to complement it critically from the standpoint of the "ethics of care", and ethics based on psychoanalytic conceptions of the subject and their suffering, which highlights the subject's dimensions as "between" social progress and "between" subjective or "between sense". Based on the guidelines of the National Health System and on the psychoanalysis of the Freudian field, the aim is to justify the ethics of the Psychosocial Care Clinic as the ethics of "self-care" - the necessary basis for the construction of the protagonism of the subjects of suffering in the production of the necessary meaning to overcome suffering and other dilemmas that motivated them to seek help, and also for the possibility of repositioning them on "between social" and "between sense"; health components in line with singularized subjectivity, referenced in socio-cultural ideals and in the desiring future. It is shown that this ethics demands from field workers the dialectical overcoming of the health and subjectivity production modes in line with the capitalist mode of production and its authoritarian derivatives.